2023
DOI: 10.3390/ijms24031906
|View full text |Cite
|
Sign up to set email alerts
|

Advancing PHBV Biomedical Potential with the Incorporation of Bacterial Biopigment Prodigiosin

Abstract: The quest for sustainable biomaterials with excellent biocompatibility and tailorable properties has put polyhydroxyalkanoates (PHAs) into the research spotlight. However, high production costs and the lack of bioactivity limit their market penetration. To address this, poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) was combined with a bacterial pigment with strong anticancer activity, prodigiosin (PG), to obtain functionally enhanced PHBV-based biomaterials. The samples were produced in the form of films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…The bands representing the axial deformation of the C-O and C-C bonds are present at 1275, 1052 cm -1 and 979 cm -1 respectively (Figure 3), whereas this broadening and increased intensity in the bands allocated at 1050 cm -1 may suggest some interaction and presence of cellulose in the PHBV/CE composite 28,29 . Studies of PHBV loaded with performed by Yu et al 30 , Yu and Qin 31 and Ponjavic et al 32 , presented similar spectra to that observed by us.…”
Section: Resultssupporting
confidence: 84%
“…The bands representing the axial deformation of the C-O and C-C bonds are present at 1275, 1052 cm -1 and 979 cm -1 respectively (Figure 3), whereas this broadening and increased intensity in the bands allocated at 1050 cm -1 may suggest some interaction and presence of cellulose in the PHBV/CE composite 28,29 . Studies of PHBV loaded with performed by Yu et al 30 , Yu and Qin 31 and Ponjavic et al 32 , presented similar spectra to that observed by us.…”
Section: Resultssupporting
confidence: 84%
“…The degradation of PHA proceeds via an abiotic route through hydrolysis of ester bonds. These novel materials find applications in orthopedics, tissue engineering, drug delivery, biomedical devices, and artificial organs [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Degradable Polymersmentioning
confidence: 99%
“…In a very recent study, a bacterial polyester PHBV and bacterial pigment Prodigiosin (PG) were produced using a simple solvent casting method [ 46 ], as illustrated in Figure 4 .…”
Section: Degradable Polymersmentioning
confidence: 99%
“…Additionally gaining popularity as a potential drug release platform are polymeric thin films. Prodigiosin (PG), a bacterial pigment with potent anticancer properties, was coupled with poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) to create functionally improved PHBV-based biomaterials [ 236 ]. The acquired samples were made using a straightforward solvent casting technique, and had a film thickness ranging from 115.6 to 118.8 µm.…”
Section: Promising Applications Of Nanomembranes and Nanoparticles In...mentioning
confidence: 99%